2005
DOI: 10.1097/01.bsd.0000177957.11603.5c
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Collapse in Thoracolumbar Burst Fractures

Abstract: In this cohort of patients, fractures that were categorized as "stable" and not requiring surgery were studied for the purpose of determining differential collapse patterns in anatomically distinct areas of the lumbar spine. We have demonstrated that the thoracolumbar junction and the midlumbar spine behave differently biomechanically and recommend that these two anatomic levels be studied independently for research purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 15 publications
0
21
0
1
Order By: Relevance
“…Th ese formulae are considerably diff erent from those associated with non-surgically treated fractured vertebrae, cited above [9]. At the same time, it is apparent that the variation between the diff erent spinal segments for the same surgery type is smaller.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…Th ese formulae are considerably diff erent from those associated with non-surgically treated fractured vertebrae, cited above [9]. At the same time, it is apparent that the variation between the diff erent spinal segments for the same surgery type is smaller.…”
Section: Discussionmentioning
confidence: 76%
“…As we have mentioned before, Fahad K. Al-Khalifa et al [9] found that the collapse of a fractured vertebra treated non-surgically may be to a certain extent predicted, applying the equation K f = K i + 0.5*K i for a T11-L1 level frac- tured vertebra, and K f = K i + 4° for a L2-L3 level fractured vertebra. For example, given a fracture displaying an initial kyphotic angle of 20° -which is considered by some authors as surgery treatment indication [21,22], for a T11-L1 segment position, according to the equation, the kyphotic angle would increase up to 30°.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The conservative treatment of vertebral fractures requires sequential radiographic followup to evaluate the potential deterioration of posttraumatic lordosis and loss of vertebral height [1013]. Changes to the individual treatment protocols and possible secondary surgical intervention often rely on the accurate assessment of the segmental and/or overall Cobb angle.…”
Section: Discussionmentioning
confidence: 99%